IMPLEMENTASI SISTEM MONITORING ASAP ROKOK MENGGUNAKAN SMARTPHONE BERBASIS IOT - Nanang Setiyawan; Andi Maslan (Computer Science and Industrial Engineering, 2024)
Cigarette smoke not only reduces indoor air quality but is very dangerous for the health of both those who smoke and those around them. The chemicals contained in cigarette smoke can cause disease to attack the body. Several actions to reduce the impact of cigarette smoke, such as the government's policy of making pictures of mouth cancer on cigarette packs, writing and pictures prohibiting smoking are often ignored by smokers so they are still seen smoking in public places. Previous research showed that monitoring systems in the form of SMS text messages and website-based applications were still deemed to be less effective. Therefore, in this research, a cigarette smoke detector was built in a closed room using the MQ-2 sensor and the SHARP GP2Y1010AUOF smoke sensor as a smoke detector and controlled using Arduino Uno and NodeMCU V3. Sensor reading values are sent using an internet connection then stored in real time in the Firebase database and displayed on the Android smartphone application. If the sensor detects cigarette smoke, the application provides a notification on the application and a buzzer sounds on the device.